Flexible Copper-7,7,8,8 Tetracyanochinodimethane Memory Devices - Operation, Cross Talk and Bending - Novak, Michael; Burkhardt, Martin; Jedaa, Abdesselam; Halik, Marcus (Thin Solid Films, 2010)
Non-volatile memory devices based on the charge transfer complex copper-7,7,8,8 tetracyanochinodimethane were fabricated on ridged and flexible substrates with special emphasis on their general functionality and cross talk behaviour in 4 × 4 passive matrix arrays. Device characteristics have been investigated at elevated temperatures during operation (ranging from room temperature to 120 °C) under ambient conditions without encapsulation. To explore the influence of mechanical stress on device performance, the memory cells on flexible polyethylene terephthalate substrates were bended during operation, up to a convex and concave radius of 4 mm. The detected shift of the switching voltages and the decrease of reliability can be attributed to stress induced cracks in the active layer.